An EDUCATION Letter (LEARNing Landscapes, 2010)
Drawing on some well-known educational thinkers, this letter to grandchildren argues that education is primarily a human ideal and activity aimed at helping all of us become better, or "educated people."Grandfather further argues that, in our world, all of us are on a lifelong journey to a somewhat illusionary but worthwhile destination, democratic citizenship. He then provides them with some "wayfinders" to aid them on their educational journey, those being virtue, relationships, responsibility and judgment which he claims are the achievements and obligations of educated people. He then promises to help them on their way.
Keywords: democratic citizenship; education; life-long journey; virtue; relationship; responsibility